Michael Thompson's Contribution to Making Social Science More Social and Scientific - VERWEIJ, Marco (Institutional Knowledge at Singapore Management University, 2004)
Good social and political theory is parsimonious, cumulative, counter‐intuitive, and relevant to well‐intended efforts to solve gripping social problems. This introduction to the Festschrift shows that in developing ‘rubbish theory’ and ‘cultural theory’ the work of Michael Thompson meets all these criteria. Added is a ‘top 10’ of quotes from Thompson's work, an overview of his academic career, as well as a bibliography.